2015
DOI: 10.1002/ajhb.22750
|View full text |Cite
|
Sign up to set email alerts
|

Developmental trajectories of aggressive behavior in children from ages 8 to 10: The role of sex and hormones

Abstract: Our results highlight the importance of studying aggressive behavior from a longitudinal perspective, taking into account sex differences and biological measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 71 publications
0
9
0
4
Order By: Relevance
“…Prior research has found a positive association between various steroid hormones (testosterone and cortisol) and aggressive behavior in children across different age groups (Azurmendi et al, 2016; Lerner et al, 2007; Sánchez-Martín et al, 2000), a finding which has prompted some authors to postulate that said hormones contribute to the development and maintenance of aggression in school-aged children. Nevertheless, the results of this present study seem to demonstrate that it is psychological factors (anger and empathy) that best define or discriminate the psychobiological profile linked to aggressive behavior, more so than hormone ones, since under equal biological conditions (higher testosterone and cortisol levels), subjects with higher levels of anger and lower levels of empathy were found to be more aggressive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research has found a positive association between various steroid hormones (testosterone and cortisol) and aggressive behavior in children across different age groups (Azurmendi et al, 2016; Lerner et al, 2007; Sánchez-Martín et al, 2000), a finding which has prompted some authors to postulate that said hormones contribute to the development and maintenance of aggression in school-aged children. Nevertheless, the results of this present study seem to demonstrate that it is psychological factors (anger and empathy) that best define or discriminate the psychobiological profile linked to aggressive behavior, more so than hormone ones, since under equal biological conditions (higher testosterone and cortisol levels), subjects with higher levels of anger and lower levels of empathy were found to be more aggressive.…”
Section: Discussionmentioning
confidence: 99%
“…McBurnett et al, 2000), there are also several studies which have observed a positive association between these two variables (e.g. Azurmendi et al, 2016; Barzman et al, 2013).…”
mentioning
confidence: 94%
“…However, in adolescence anxiousness may even become a risk factor for late onset or aggravation of offending (Loeber et al, 2008;Zara and Farrington, 2009). Some research suggests that an increase of cortisol in late childhood relates to an increase in aggressive behavior, but estradiol may have a buffering effect (Azurmendi et al, 2016).…”
Section: The Role Of Protective Factorsmentioning
confidence: 99%
“…Ahora bien, en cuanto a la asociación entre las variables de estudio. Específicamente, la asociación positiva entre las CAR (dieta, atracón-purga y control oral) y la habilidad social en las mujeres (es decir a mayor CAR mayores puntuaciones del CABS [agresividad]), desde la biología se ha explicado que las personas quienes practican CAR o quienes tienen TCA, presentan altos niveles de Cortisol por lo que tienden a la agresividad (Warren, 20011) y recientemente, se ha encontrado una relación positiva entre esta hormona y la agresividad (Azurmendi et al, 2016;Pacheco, 2017). Considerando el aspecto psicológico, se ha encontrado que personas quienes llevan a cabo CAR suelen tener mayor dificultad en el manejo emocional y de socialización por lo que puede verse reflejada la agresividad consigo mismas y con las demás personas (Cruz-Sáez, Pascual, Extebarría, & Echeburúa, 2013;Romero et al, 2015).…”
Section: Autoes Ma Y Ansiedad Estado-rasgo En Adultos Universitarios unclassified